Peningkatan Kompetensi Bermain Musik Keroncong Guru Sekolah Dasar di Kabupaten Banjarnegara - SLAMET HARYONO; Langlang Handayani; Suharto; Wadiyo; Indi Purnomo; Gita Surya Shabrina; Maulana Resha Vivadi; Elsya Wynsa Maharani Putri (Fakultas Komputer dan Pendidikan Universitas Ngudi Waluyo, 2022)
Keroncong is one of the cultural heritages owned by Banjarnegara, which needs to be preserved through education, especially in elementary schools. However, the competency in playing keroncong music for teachers is not sufficient, so it is necessary to hold a keroncong training program for teachers. This keroncong training aims to increase the knowledge and skills of teachers in playing keroncong music. The main stage of the activity is programmed training, which consists of planning steps, training implementation, and independent practice. The planning step includes identifying the types of activities for training, material development and implementation design, as well as preparing supporting facilities, while in the training implementation step a workshop is held which includes presentation of material on keroncong music, individual and group practice in the training arena accompanied by the implementing team. In the independent practice step, participants practice playing keroncong music in groups using the available instruments. From a series of community service activities, it can be concluded that the teacher's knowledge and skills in playing keroncong music have increased. The participants managed to play the cak, cuk, cello and bass instruments well to accompany the keroncong song they were singing. As a follow-up to the activity, it is suggested to carry out keroncong music learning training for elementary school teachers and provide a set of Keroncong musical instruments in schools as a means for teachers to teach them to students. AbstrakKeroncong merupakan salah satu warisan budaya yang dimiliki oleh Banjarnegara, yang perlu dilestarikan keberadaannya melalui jalur Pendidikan, khususnya di sekolah dasar. Namun demikian, kompetensi bermain musik keroncong para guru belum memadai sehingga perlu diadakan program pelatihan keroncong bagi guru. Pelatihan keroncong ini bertujuan untuk meningkatkan pengetahuan dan keterampilan guru dalam bermain musik keroncong. Tahapan utama kegiatan adalah pelatihan terprogram, yang terdiri dari langkah-langkah perencanaan, pelaksanaan pelatihan, dan praktek mandiri. Langkah perencanaan meliputi identifikasi jenis kegiatan untuk pelatihan, pengembangan materi dan rancangan pelaksanaan, serta penyiapan fasilitas pendukung, sementara pada langkah pelaksanaan pelatihan dilaksanakan workshop yang meliputi pemaparan materi tentang musik keroncong, praktek individu, dan kelompok di arena pelatihan didampingi oleh tim pelaksana. Pada langkah praktek mandiri, peserta mempraktekkan bermain musik keroncong secara berkelompok dengan menggunakan instrument yang tersedia. Dari rangkaian kegiatan pengabdian dapat disimpulkan bahwa pengetahuan dan keterampilan guru dalam bermain musik keroncong mengalami peningkatan. Peserta berhasil memainkan instrumen cak, cuk, cello dan bass dengan baik untuk mengiringi lagu keroncong yang dinyanyikan. Sebagai tindak lanjut kegiatan, disarankan untuk dilaksanakan pelatihan pembelajaran musik keroncong bagi guru sekolah dasar dan menyediakan seperangkat alat musik Keroncong di sekolah sebagai sarana guru untuk membelajarkannya bagi siswa.